Obstructive sleep apnea and blood pressure elevation: what is the relationship? Working Group on OSA and Hypertension. - Carlson, J; Davies, R; Ehlenz, K; Grunstein, R; Hedner, J; Podszus, T; Sinoway, L; Stradling, J; Telakivi, T; Zwillich, C (1993)
Sleep disordered breathing has increasingly been recognised as a frequent cause of ill-health in the community. Moderate or severe forms of the most common condition, obstructive sleep apnea (OSA), occur in up to 12% of the adult male population. A substantial body of literature has been published on the potential relationship between OSA and cardiovascular disease. In particular, OSA has been associated with cardiac failure, stroke, myocardial infarction and hypertension. Part of this association may be explained by other confounders, mainly obesity, which is common in OSA patients. The present review was prepared following a workshop aimed to critically review available scientific evidence suggesting that hypertension is a direct consequence of OSA. In addition, pathophysiologic mechanisms that may be involved in the relationship between OSA and cardiovascular disease, particularly brief intermittent elevation of blood pressure and sustained systemic hypertension, are discussed.